Pengaruh Desain Produk, Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian pada Produk Handphone Merek Oppo - Hidayat, Rahmat; Indayani, Lilik (Journal of Empowerment and Community Service (JECSR), 2024)
This study aims to determine that product design, brand image and product quality influence purchasing decisions on Oppo brand mobile phones. This research uses quantitative research with hypothesis testing. The sampling technique used in this study used a non-probability sampling technique with an accidental sampling method of 96 respondents. And the data analysis technique uses data quality test, classical assumption test, and multiple linear regression analysis. The results of this study indicate that product design and product quality have a significant effect on purchasing decisions, while brand image has no effect on purchasing decisions.